(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The main aim of the present study is to find out about allergenic fungal spores concentration in Dr.B.R.Ambedkar Open University, during the monsoon, pre-winter seasons of 2022 through the spider web analysis. Twelve allergenic fungal spores viz., Cladosporium sp., Alternaria sp., Ascospores , Ganoderma sp.,Dipolodia sp., Pithomyces sp., Curvularia sp.,Spegazzinia sp.,Coprinus sp.,Nigrospora sp.,Tetraploa sp.,Kretzschmaria sp.,which cause allergic rhinitis to human beings, were recorded from representing locality. Among the fungal diversity, Alternaria sp. (26.21%) was the most abundant fungal spore type, next predominant fungal spores were Curvularia sp. (22.65%).